Effect of prednisolone on live birth rate in women with unexplained recurrent pregnancy loss: a study protocol for a double-blind, placebo-controlled, multicentre, randomised controlled trial (PREMI-study) - Saskia le Cessie; Nan van Geloven; Marie-Louise van der Hoorn; Michael Eikmans; Annemarie Mulders; Eileen Lashley; Jantien Visser; Moniek van der Zanden; Mariette Goddijn; Tess Meuleman; Salwan Al-Nasiry; Harold Verhoeve; et al. (BMJ Open)
Introduction Recurrent pregnancy loss (RPL) is defined as the occurrence of two or more spontaneous pregnancy losses from the time of conception until 24 weeks of gestation. Currently, an underlying cause can be identified in only a minority of the losses. Potentially, an impaired maternal immune response targeting the semiallograft pregnancy may lead to miscarriage. While prior studies have explored the use of immune-suppressing corticosteroids to modulate the maternal immune system and hopefully improve pregnancy outcome, the absence of sufficiently powered randomised controlled trials (RCT) underscores the need for further research. The primary aim of this study is to evaluate if prednisolone administration in early pregnancy (20 mg daily for 6 weeks, then tapering doses for 2 weeks) in women with unexplained RPL leads to a higher live birth rate (LBR) in comparison to placebo. Additionally, the study assesses the tolerability, safety and the cost-effectiveness of this intervention. Finally, we will explore the effect of prednisolone in various subgroups (based on maternal age, number of previous pregnancy losses, presence of specific antibodies and pre-pregnancy endometrial immune cell level).Methods and analysis This ongoing multicentre, double-blind RCT will randomise 490 women with unexplained RPL and pregnancy <7 weeks to receive either prednisolone or placebo. Each participant will be followed up for 1 year, with digital questionnaires to assess depression, anxiety, medical expenses and productivity loss. We will also collect data on maternal and paternal demographics and neonatal outcomes. The sample size of 490 participants was calculated according to a minimally important increase in LBR of 12% (expecting a LBR of 63% in the general RPL population), including loss to follow-up (estimated at 5%). The analysis will follow the intention-to-treat principle.Ethics and dissemination This study was submitted under the Clinical Trial Regulation (CTR) in Clinical Trials Information System (CTIS) for assessment by the Central Committee on Research Involving Human Subjects (CCMO) under Clinical Trial number: 2023-503220-76-01. It received full approval on 29/01/2024. Study findings will be presented at conferences and published in a peer-reviewed journal. Participants will be informed about the results by publishing them on the publicly available website of the study.Trial registration number This trial is registered in ClinicalTrials.gov (ID NCT05725512) and in CTIS (2023-503220-76-01).